Comparison of Dural Puncture Epidural, Epidural and Combined Spinal-Epidural Anesthesia for Cesarean Delivery: A Randomized Controlled Trial - Rao WY; Xu F; Dai SB; Mei Z; Chen XP; Lv CC; Liu CL; Ngan Kee W; Chen XZ (Dove Medical Press, 2023)
Wan-Yi Rao,1,* Fang Xu,1,* Shao-Bing Dai,1 Zhong Mei,2 Xiao-Ping Chen,1 Chang-Cheng Lv,1 Chun-Lei Liu,1 Warwick Ngan Kee,1 Xin-Zhong Chen1 1Department of Anesthesia, Women's Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Department of Anesthesiology, Affiliated Xiaoshan Hospital, Hangzhou Normal University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin-Zhong Chen, Department of Anesthesia, Women's Hospital, Zhejiang University School of Medicine, No. 1 Bachelor's Road, Hangzhou, 310000, People's Republic of China, Email chenxinz@zju.edu.cnPurpose: Catheter-based techniques such as combined spinal-epidural (CSE) anesthesia which are sometimes indicated for obstetric anesthesia have a complex mechanism of action. The application of the dural puncture epidural (DPE) anesthesia for cesarean section (CS) has not been well investigated. The present study compared the relatively novel DPE technique with epidural (EA) and CSE anesthesia.Patients and Methods: We randomly assigned 150 parturients who underwent elective CS to receive DPE, EA or CSE anesthesia. The primary outcome was the onset of sensory anesthesia to the T5 dermatome assessed using the Cox proportional hazards model. Secondary outcomes included median time to sensory block, quality of block, patient and surgeon satisfaction, APGAR scores and other side effects.Results: For DPE anesthesia versus EA anesthesia, the onset of anesthesia was faster (hazard ratio 2.47 [95% CI 1.56 to 3.90], adjusted P < 0.001) and the median time to surgical level was shorter (16 [IQR 14- 18] min versus 19 [15.5- 21] min, adjusted P < 0.001); the incidence of intraoperative pain was lower (7/48 versus 17/47, adjusted P = 0.046) and the median patient satisfaction score was higher (9 [IQR 9- 10] versus 8 [8- 9.5], adjusted P = 0.004). In the CSE group, the onset of anesthesia was faster than in the other two but the incidence of hypotension was higher (P < 0.001) and the phenylephrine requirement was greater (P < 0.001).Conclusion: DPE anesthesia had a faster onset and better quality of block than EA anesthesia and provided less influence to maternal hemodynamic parameters than CSE anesthesia for CS. These results suggest that the dural puncture plays a significant role in enhancing the effectiveness of epidural top-ups during CSE anesthesia and indicates enlightenment that contributes to the satisfaction of anesthetic effect in DPE technique labor analgesia transferred to CS.Keywords: anesthesia, dural puncture epidural, anesthesia, epidural, cesarean section